Efeito agudo dos modelos de ensino e aprendizagem na fadiga mental, atenção e tomada de decisão em atletas jovens de voleibol de praia - Lacerda, Wigna Gouveia de (2025)
Introduction: Teaching-learning models influence not only technical-tactical performance but also cognitive aspects relevant to sports, such as mental fatigue, attention,and decision-making. Objective: To analyze the acute effects of different teaching-learning models (analytical, hybrid, and situational) on mental fatigue, attention, and decision-making in young beach volleyball athletes. Materials and Methods: This is a quasi-experimental study with a randomized crossover design. The sample consisted of twenty-four female athletes who were exposed to three experimental conditions (analytical, hybrid, and situational models), with a seven-day washout period between each. Mental fatigue was assessed using a Visual Analogue Scale (VAS), attention with the Trail Making Test B, and decision-making through performance analysis in game complexes I and II. Results: All models significantly increased mental fatigue, with the situational model showing the highest overload. No statistically significant differences were found in attention or decision-making, although the hybrid model showed higher average scores. Conclusion: Different teaching- learning models generate distinct cognitive demands, with the situational model inducing greater mental fatigue. The hybrid model appears to be a promising strategy for balancing technical-tactical demands with lower immediate mental overload.